Multi-site red-edge excitation shift reveals the residue-specific solvation dynamics during the native to amyloid-like transition of an amyloidogenic protein - More, Sonal R.; Jha, Santosh Kumar (Journal of Physical Chemistry B, 2024)
Changes in water-protein interactions are crucial for proteins to achieve functional and nonfunctional conformations during structural transitions by modulating local stability. Amyloid-like protein aggregates in deteriorating neurons are hallmarks of neurodegenerative disorders. These aggregates form through significant structural changes, transitioning from functional native conformations to supramolecular cross-beta-sheet structures via misfolded and oligomeric intermediates in a multistep process. However, the site-specific dynamics of water molecules from the native to misfolded conformations and further to oligomeric and compact amyloid structures remain poorly understood. In this study, we used the fluorescence method known as red-edge excitation shift (REES) to investigate the solvation dynamics at specific sites in various equilibrium conformations en route to the misfolding and aggregation of the functional domain of the TDP-43 protein (TDP-43tRRM). We generated three single tryptophan-single cysteine mutants of TDP-43tRRM, with the cysteines at different positions and tryptophan at a fixed position. Each sole cysteine was fluorescently labeled and used as a site-specific fluorophore along with the single tryptophan, creating four monitorable sites for REES studies. By investigating the site-specific extent of REES, we developed a residue-specific solvation dynamics map of TDP-43tRRM during its misfolding and aggregation. Our observations revealed that solvation dynamics progressively became more rigid and heterogeneous to varying extents at different sites during the transition from native to amyloid-like conformations.